Organic Chemicals : An Environmental Perspective - Neilson, Alasdair H. (CRC Press, 2009)
Environmental problems have become increasingly complex. The procedures for investigating these problems cross the traditional boundaries of organic and analytical chemistry, microbiology and biology. Organic Chemicals: An Environmental Perspective brings together the basic issues of chemical analysis, distribution, persistence, and ecotoxicology.